Rice trade liberalization and poverty - Gulati, Ashok; Narayanan, Sudha (2003)
Rice is the lifeline of almost 70% of the world’s poor residing in Asia, where more than 90% of world rice production and consumption takes place. Rice trade liberalization therefore has tremendous implications for poverty. The world rice market is highly distorted, partly because of the high degree of intervention in rice markets across the world. While poor countries such as Thailand, Vietnam, and India tend to “disprotect” rice sectors, the rich countries of East Asia (Japan and Korea), Europe, and the United States heavily support their rice producers. As a result, there is great diversity in domestic rice price levels, with very high prices in the latter countries and very low prices in the former. Trade liberalization would thus result in flows from these poorer Asian countries to East Asia and Europe. This is predicted to have beneficial effects for poverty, through producer price increases and second-round effects (wages, employment, and investment) in exporting countries, and to augment short-term food security in poor importing countries. However, if rice trade liberalization is to contribute to poverty alleviation in developing countries, there is a need to streamline distortionary agricultural policies, particularly in developed countries. Also important are “behind the border” reforms in developing countries aimed at reducing transactions costs for farmers, rationalizing input pricing policies, ensuring access to risk management institutions and safety nets, improving access to food, and combating adverse environmental conditions. In the long run, rice trade liberalization might have to be coupled with initiatives to enhance agricultural productivity and rural economic growth to be able to make a dent in poverty.